2012
DOI: 10.1080/10807039.2012.688719
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Convictions and Trust for Public Protest Potential in the Case of Carbon Dioxide Capture and Storage (CCS)

Abstract: For the public to accept new technologies, trust and convictions play an important role. In the present research, we used structural equation modeling to examine an extensive causal model of the role of convictions and trust for the public's protest potential against carbon dioxide capture and storage (CCS) among a large sample of the general population (N = 769). Trust, convictions, perceived benefits, and risks were included in the model. Our model fitted the data well. Convictions regarding emission reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Theoretically, local residents’ acceptance of SGE can be improved by their positive beliefs since SGE contributes to local development by increasing employment and income opportunities, improving public infrastructures, and fostering community pride [ 23 , 24 , 25 ]. Moreover, local residents’ acceptance of SGE can also be weaken by their negative beliefs as SGE poses a level of threat to health and environment, especially when the regulations are not sufficient to address these threatens [ 25 , 26 , 27 ]. Therefore, the following hypotheses are proposed.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Theoretically, local residents’ acceptance of SGE can be improved by their positive beliefs since SGE contributes to local development by increasing employment and income opportunities, improving public infrastructures, and fostering community pride [ 23 , 24 , 25 ]. Moreover, local residents’ acceptance of SGE can also be weaken by their negative beliefs as SGE poses a level of threat to health and environment, especially when the regulations are not sufficient to address these threatens [ 25 , 26 , 27 ]. Therefore, the following hypotheses are proposed.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Drawing together many of these ideas, the notion of 'tampering with nature' addresses humans' interference in the natural world combined with the arrogance or immorality that such acts may reflect (Sjöberg, 2000). A further CCS study in Switzerland found that tampering with the subsurface was a particularly influential value construct, suggesting a 'moral concept' of nature (and the subsurface in particular) ranging from 'naturally untouched' to 'un-naturally disturbed' (Wallquist et al, 2012). Such a framework aligns with the established finding that views on emergent technologies are influenced by perceived (un)naturalness (Slovic, 2000;Corner et al, 2013).…”
Section: Energy Initiatives and 'Tampering With The Underground'mentioning
confidence: 99%
“…Nevertheless, the transferability of results from international studies to the German context is limited. While in most countries CCS is also linked to energy as well as other industry sectors (such as the production of cement and steel; Barker et al, 2009;Wang et al, 2007;Xu and Cang, 2010), the German debate has focussed solely on coal (BMBF, 2007;Skrylnikow, 2010). From the beginning, CCS was seen as the saviour of the coal-mining industry and energy production through coal (Praetorius and Stechow, 2009).…”
Section: Introductionmentioning
confidence: 99%